Penggunaan Metode Respondent Driven Sampling (Rds) dalam Survey Pemasaran Beras di Provinsi Kepulauan Riau - Pudjihastuti, Herena (Bina Nusantara University, 2014)
As a Free Trade Zone (FTZ), the province of Riau Islands has a different pattern of strategic commodity (such as rice) marketing comparing to other regions in Indonesia. To anticipate and control the negative effects of the implementation of FTZ policy, It is necessary to study about rice marketing trade system in the Riau Islands region. The study was conducted to identify patterns of supply and marketing of food (rice) and analyze the marketing margin and marketing efficiency as well as the factors that influence it. The study was conducted through desk study and field surveys. Secondary data was collected from various sources and primary data collected through interviews with selected respondents using Respondent Driven Sampling method (RDS). The study shows that the structure of the rice market in Riau Islands can be categorized as monopolistic. Most of the rice supply comes from outside the region and import, the supply chain is quite simple, the price is relatively stable and relatively efficient marketing and resilience of rice reserves are relatively high for merchants. Nevertheless, the Riau islands will be very susceptible to interference distribution. Required efforts of the provincial government of Riau Islands to provide sufficient rice reserves. This paper gives an example of the use of the RDS method in marketing surveys.